Diversity of Soil Macrofauna in Liberica Coffee Plantation (Coffea liberica) in Lerek Gombengsari Village, Banyuwangi - Mawimuawanah, Rafika Resti; Gama, Zulfaidah Penata (Journal of Coffee and Sustainability, 2024)
This study aims to identify the diversity and role of soil macrofauna in Liberica coffee plantations. Samples were taken from two coffee plantations in Lerek Village. Abiotic measurements were taken on each field. Samples were taken using the hand-sorting method. Data analysis uses the importance index, Shannon-Wiener diversity, evenness, dominance, richness, and Spearman correlation test. Based on the results of the study, there were 18 families of soil macrofauna. The family Megascolecidae occupies the highest importance index on both lands. The diversity index on dark land is 1.94 and light land is 1.95, which both fall into the medium category. The dominance index of dark land is 0.24 and light land is 0.21, which means that both lands do not have dominant species. The evenness index of dark land is 0.67, and light land is 0.74, which means that it has a relatively equal or evenly distributed level. The richness index of dark land is 3.18 in the medium category, and light land is 2.46 in the low category. The role of soil macrofauna on dark land 88% detritivore, 8% herbivore, 4% carnivore, and on light land is 85% detritivore, 12% herbivore, and 3% carnivore.